Anterior and middle superior alveolar nerve block for anesthesia of maxillary teeth using conventional syringe - Ignacio Velasco; Reinaldo Soto (Wolters Kluwer Medknow Publications, 2012)
Background: Dental procedures in the maxilla typically require multiple injections and may inadvertently anesthetize facial structures and affect the smile line. To minimize these inconveniences and reduce the number of total injections, a relatively new injection technique has been proposed for maxillary procedures, the anterior and middle superior alveolar (AMSA) nerve block, which achieves pulpal anesthesia from the central incisor to second premolar through palatal approach with a single injection. The purpose of this article is to provide background information on the anterior and middle superior alveolar nerve block and demonstrate its success rates of pulpal anesthesia using the conventional syringe. Materials and Methods: Thirty Caucasian patients (16 men and 14 women) with an average age of 22 years-old, belonging to the School of Dentistry of Los Andes University, were selected. All the patients received an AMSA nerve block on one side of the maxilla using the conventional syringe, 1 ml of lidocaine 2% with epinephrine 1:100.000 was injected to all the patients. Results: The AMSA nerve block obtained a 66% anesthetic success in the second premolar, 40% in the first premolar, 60% in the canine, 23.3% in the lateral incisor, and 16.7% in the central incisor. Conclusions: Because of the unpredictable anesthetic success of the experimental teeth and variable anesthesia duration, the technique is disadvantageous for clinical application as the first choice, counting with other techniques that have greater efficacy in the maxilla. Although, anesthetizing the teeth without numbing the facial muscles may be useful in restorative dentistry.